2022
DOI: 10.26434/chemrxiv-2022-9213j
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benchtop 19F nuclear magnetic resonance spectroscopy enabled kinetic studies and optimization of the synthesis of carmofur

Abstract: Carmofur, a 5-fluorouracil derivative, was initially developed as an antineoplastic agent to treat colorectal cancer. Through drug repurposing efforts, it has been identified as a potent covalent inhibitor of the main protease of SARS-CoV-2 (Mpro), making it a promising therapeutic agent against COVID-19. However, previous synthetic procedures suffer from low yields, or long reaction times. In this study, benchtop 19F nuclear magnetic resonance spectroscopy (NMR) enables the real-time quantitative monitoring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…An initial screen of a variety of Lewis acid catalysts revealed that 8 mol % ytterbium­(III) triflate in acetonitrile most efficiently catalyzed the Biginelli condensation between ethyl 4,4,4,-trifluoroacetoacetate, thiourea, and 3-hydroxybenzaldehyde to the corresponding tetrahydropyrimidinone (Table ). …”
Section: Resultsmentioning
confidence: 99%
“…An initial screen of a variety of Lewis acid catalysts revealed that 8 mol % ytterbium­(III) triflate in acetonitrile most efficiently catalyzed the Biginelli condensation between ethyl 4,4,4,-trifluoroacetoacetate, thiourea, and 3-hydroxybenzaldehyde to the corresponding tetrahydropyrimidinone (Table ). …”
Section: Resultsmentioning
confidence: 99%
“…From the onset, we found that the trifluorinated ketoester was a convenient spectroscopic handle on benchtop 19 F nuclear magnetic resonance (NMR) spectroscopy for real time, quantitative analysis of the rates of formation and absolute concentrations of reaction intermediates and product formation as a function of time. Since these instruments do not require deuterated solvents with proton lock capabilities, crude reaction mixtures or reaction aliquots could be directly analyzed in the instrument without further processing, and on analytical scale, reactions could themselves be performed in standard 5 mm NMR tubes for rapid, high throughput reaction condition screening and optimization (Figure 1c), and indeed we previously reported the use of 19 F NMR spectroscopy for reaction condition optimization for a scalable synthesis of other fluorinated small molecules [26]. To make this workflow quantitative, reaction mixtures were spiked with an internal standard, and for the purposes of this study, α,α,α-trifluorotoluene was selected over hexafluorobenzene as an internal standard.…”
Section: Resultsmentioning
confidence: 99%
“…From the onset, we found that the trifluorinated ketoester was a convenient spectroscopic handle on benchtop 19 F nuclear magnetic resonance (NMR) spectroscopy for real time, quantitative analysis of the rates of formation and absolute concentrations of reaction intermediates and product formation as a function of time. Since these instruments do not require deuterated solvents with proton lock capabilities, crude reaction mixtures or reaction aliquots could be directly analyzed in the instrument without further processing, and on analytical scale, reactions could themselves be performed in standard 5 mm NMR tubes for rapid, high throughput reaction condition screening and optimization (Figure 1c), and indeed we previously reported the use of 19 F NMR spectroscopy for reaction condition optimization for a scalable synthesis of other fluorinated small molecules [33]. To make this workflow quantitative, reaction mixtures were spiked with an internal standard, and for the purposes of this study, α,α,α-trifluorotoluene was selected over hexafluorobenzene as an internal standard.…”
Section: Resultsmentioning
confidence: 99%